Targeting the AMP-activated protein kinase pathway: the active metabolites of botanical drugs represent potential strategies for treating metabolic-associated fatty liver disease - Liang, Qi; Ai, Li; He, Lin; Wang, Liang-Chen; Wang, Jiao-Long (Frontiers in Pharmacology, 2026)
AMP-activated protein kinase (AMPK) is capable of regulating cellular energy homeostasis and mitochondrial homeostasis. The activation of AMPK can ameliorate metabolic-associated fatty liver disease (MAFLD). An increasing number of studies have demonstrated that AMPK is a crucial enzyme in the regulation of glucose and lipid metabolism in the body, and numerous botanical drugs act as AMPK activators. This activation can alleviate glucose and lipid metabolism disorders, reduce oxidative stress, and serve as a pivotal therapeutic target for metabolic diseases. MAFLD represents the liver-related manifestation of metabolic syndrome. Currently, there are well - established antidiabetic drugs in clinical practice, yet they also entail side effects. A substantial number of in vitro and in vivo experimental studies have indicated that natural traditional Chinese medicine targeting AMPK holds promising prospects in the treatment of MAFLD. In this paper, literature was retrieved through electronic databases, including the Web of Science, PubMed, Google Scholar, Springer, and CNKI (Chinese). Therefore, with AMPK as the target, this article analyzes and summarizes the process and mechanism by which botanical drugs activate AMPK to improve glucose and lipid metabolism disorders and mitochondrial homeostasis disorders, aiming to offer a broader perspective for the development of botanical drugs for MAFLD.